(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: The Swedish model for Physical Activity on Prescription (PAP-S) is an established Swedish method and a valuable tool for prescribing physical activity. It has been used within the Swedish healthcare system for 20 years. As part of national efforts to reverse the negative trend of physical inactivity in the population, the Swedish government assigned the Swedish National Board of Health and Welfare together with the Public Health Agency of Sweden to enhance the work with PAP-S. The overarching aim was to ensure that PAP-S is applied more equitably across the country and is offered to all patients in primary health care in need, to help increase their level of physical activity and promote good health. The aim was also to support and develop monitoring for PAP-S as well as to strengthen the conditions for a long-term follow-up of the work at the regional level. Project Description: The assignment involved allocating funds to the regions to work on initiatives to increase the prescription of physical activity, promoting adherence to prescribed physical activity, supporting implementation, developing follow-up procedures for PAP-S and revision of national guidelines for unhealthy lifestyle habits, including insufficient physical activity. The authorities will submit a final report to the government before the summer, after more than two years of implementation and monitoring. The report will include how the regions have used the government grants, how the use of PAP-S has been monitored and developed, as well as follow-up on the regions’ long-term efforts related to PAP. This includes national coordination, dissemination of knowledge, development of tools, and support for regional implementation. Conclusion: The assignment has been implemented over a two-year period. A final report will be submitted to the government in May 2025. Some of the main findings are that the government grant has contributed to a significant increase in usage of PAP-S in the Swedish primary health care. The follow-up has shown that the regions are making many efforts to develop the work through education, coordination, and collaboration. We will present the main results from the report in more detail and the lessons learned from the work.